RENACER study: Assessment of 12-month efficacy and safety of 168 certolizumab PEGol rheumatoid arthritis-treated patients from a Spanish multicenter national database. Issue 3 (3rd May 2016) - Torrente-Segarra, Vicenç; Urruticoechea Arana, Ana; Sánchez-Andrade Fernández, Amalia; Tovar Beltrán, Juan Víctor; Muñoz Jiménez, Alejandro; Martínez-Cristóbal, Anna; González Ferrández, José Antonio; Fernández Prada, Manuel; Vázquez Fuentes, Noelia; Corominas, Hèctor; García-Díaz, Sílvia; Acosta Pereira, Asunción; et al.
Abstract: Objective : To assess effectiveness and safety of certolizumab PEGol (CZP) in rheumatoid arthritis (RA) patients after 12 months of treatment and to detect predictors of response. Methods : Observational longitudinal prospective study of RA patients from 35 sites in Spain. Variables (baseline, 3- and 12-month assessment): sociodemographics, previous Disease Modifying Anti-Rheumatic Drug (DMARD) and previous Biological Therapies (BT) use; TJC, SJC, ESR, CRP, DAS28, SDAI. Response variables: TJC, SJC, CRP, ESR, and steroids dose reductions, EULAR Moderate/Good Response, SDAI response and remission, DAS28 remission. Safety variables: discontinuation due to side-effects. Descriptive, comparative and Logistic regression analyses were performed. Results : We included 168 patients: 79.2% women, mean age 54.5 years (±13.2 SD), mean disease duration 7.5 years (±7.3 SD). Mean number of prior DMARD: 1.4 (±1.2 SD), mean number of prior BT was 0.8 (±1.1). Mean time on CZP was 9.8 months (±3.4 SD). A total of 71.4% were receiving CZP at 12-month assessment. Baseline predictors of response: lower prior number DMARD; low number prior BT; higher CRP, ESR, TJC, SJC, DAS28 and SDAI ( p < 0.05) scores. A 25/46.4% Moderate/Good Response, a 20% SDAI remission, and a 44% DAS28 remission were observed. We observed 48 discontinuations (28.6%), 31 due to partial or complete ineffectiveness, and 17 due to side-effects. Conclusions : CZP showed benefit in severe RA patients, with significant reduction of all effectiveness parameters, despite the high prevalence of previous BT exposure in our series. We found CRP, ESR, prior DMARD/BT number, TJC, SJC, DAS28, and SDAI as baseline predictors of response. CZP was mostly well tolerated.